MEMBIDIK PRESTASI FISIKA: SINERGI KAMPUS DAN SEKOLAH DALAM MENUMBUHKAN GENERASI JUARA SAINS - Bilqis, Ayesha; Nurhanivah, Devi; Prasetia, Yuda (LPPM UKRI, 2025)
This community service program aimed to introduce high school students to the concept of physics olympiads as an effort to foster motivation and interest in scientific competition. The activity, titled “Targeting Physics Achievement: Pre-Olympiad Initiation for a Generation of Champions,” was conducted at SMA Negeri 2 Padalarang, West Bandung Regency, involving 50 students from the science track of grade XI. The implementation employed a participatory and interactive approach through academic lectures, guided problem-solving sessions, and group discussions facilitated by lecturers and students from the Physics Department of UKRI. Evaluation was carried out using a diagnostic pre-test and reflective questionnaire to identify participants’ initial understanding and perceptions of the activity. The results indicated that students gained new insights into the structure and scope of the physics olympiad and demonstrated increased enthusiasm and self-confidence to join future scientific competitions. The program also strengthened collaboration between UKRI and SMA Negeri 2 Padalarang through the signing of an Implementation of Arrangement (IA) for a follow-up physics olympiad mentoring program during the 2025/2026 academic year.